Determinants of Investment Decisions With Corporate Social Responsibility as Moderation in Indonesia Stock Exchange Manufacturing Companies - Ida Ayu Surasmi; Ida Bagus Udayana Putra; Luh Gede Ariastuti; Ni Luh Putu Martini (Jurnal Ekonomi dan Bisnis Jagaditha, 2025)
Investment decisions need attention for companies. Investment decisions are proxied with the Price Earning Ratio (PER). Price Earning Ratio. (PER) by factors such as leverage, growth opportunities, liquidity, profitability, cash flow, age of the company. In making investment decisions, in addition to considering financial factors, non-financial factors are also considerations that can legitimize the company's existence for the long term. Corporate Social Responsibility (CSR) is a consideration for investors because it is a good form of investment for the sustainability of the company's business. Based on the results of previous research related to CSR, it turns out that there is an inconsistency in the results as well as inconsistencies in the results of determinants that affect investment decisions, so there is a suspicion to include CSR as a moderation variable. The purpose of this study is to analyze the influence of PER on DAR, GROW, CR, ROA, CF, AGE and CSR as moderation variables. Based on PLS with the help of Smart PLS software version 3.0 with a total of 48 issuers of consumer sub-sector manufacturing companies for the 2020-2023 period, it shows that AGE has a significant positive effect on PER, AGE has a significant positive effect on PER, while DAR, GROW, CR, ROA and CF partially have no effect on PER. Likewise, CSR is not able to partially strengthen the influence of DAR, GROW, CR, ROA and CF on PER